MITOCHONDRIAL DYSFUNCTION AS POSSIBLE CAUSE OF IMPAIRED FOLLICULAR DEVELOPMENT - A. A. Pozdnyakova; M. A. Volodina; S. J. Rshtuni; L. A. Marchenko; M. Yu. Vysokikh (IRBIS LLC, 2016)
Mitochondria play leading role in senescence program realization. One of the early manifestations of this process is loss of reproductive function in female (menopause). In this review we discuss up-to-date data on basic mitochondria functions and their possible role in development of premature ovarian insufficienсy and morbid conditions associated with this state, that are typical for ageing organism. Besides performing function of conversion of free energy by cell respiration substrates oxidation mitochondria control survival and death of somatic cells and gametes maintaining optimal level of reactive oxygen species in cells. Oxidative stress results in selective death of specialized cells; organs and tissues functionality disturbance; leads to development of cardiovascular, locomotor and nervous disorders. The main reason of oxidative stress is mitochondrial disfunction induced by disbalance between reactive oxygen species production and their utilization by antioxidant system. On the other hand mitochondria play central role in intracellular signal transmission and maintain functional state and cellular structure of tissues, organs and systems of an organism controlling cell proliferation, differentiation and apoptosis. Finally mitochondria define largely immune response in case of infections and tumoral transformation and control sex hormones level taking part in steroidogenesis. It was found that high level of damaged mitochondrial DNA, decrease of its copy number and increase of reactive oxygen species production in ovarian tissue cells are typical for women suffering from premature ovarian insufficienсy. Chronic oxidative stress leads not only to oogenesis disturbance and decrease of oocyte maturation probability but promotes also cardiovascular diseases, osteoporosis and other delayed consequences of estrogen deficit development in case of this state.